Hybrid emplacement mechanisms and structural interactions: insights into dike-fault-fracture systems in SE Korea - Lee, Jinhyun; Kim, Goeun; Kim, Young-Seog (Frontiers in Earth Science, 2025)
The structural evolution of dike-fault-fracture (DF2) systems is governed by the combined effects of dike emplacement and structural inheritance, together with deformation that occurs after emplacement. Each magma injection can either forcefully fracture intact rock to create new pathways or passively intrude along pre-existing fractures, reflecting a hybrid dike emplacement. Integrated field mapping and topological analysis reveal hybrid emplacement mechanisms in Eocene mafic dikes intruding Late Cretaceous granitic bedrock in southeast Korea. Dikes in the study area display three distinct orientations. Geometric restoration indicates dike emplacement under NW–SE minimum principal stress. NE-striking dikes formed through forceful fracturing, creating a continuous Mode I structure. ENE- and NNE-striking dikes developed via passive intrusion along pre-existing fracture sets, producing characteristic zigzag geometries, blunt terminations, and apparent offsets. Complex dike patterns reflect hybrid emplacement combining both mechanisms under local stress-field rotations. NE-striking dikes act as both barriers to fracture propagation and strain concentrators, partitioning deformation within the host rock. Post-emplacement deformation modified the DF2 system architecture. Stress field rotation reactivated ENE-oriented fractures as sinistral faults, generating damage zones with fracture intensity (P21) up to 6.14 m−1 and a connectivity (CB) of 1.29. Post-intrusion hydrothermal alteration produced calcite veins concentrated along dike margins and ENE fault-tip and linking damage zones. Superimposed slickenlines record multiple reactivation phases, indicating continued structural evolution after magmatic emplacement. These results demonstrate that hybrid emplacement mechanisms establish structurally heterogeneous frameworks governing subsequent tectonic overprinting, highlighting the coupled evolution of magmatic and structural processes in continental crust.